The Role of Opera in Ignacio de Luzán’s Poetics. Between Tragedy and the Liberal Arts (2022)
Ignacio de Luzán wrote the most influential Spanish poetics of the 18th century, at a period when Italian opera occupied an essential place in all the courts of Europe. However, this genre receives marginal treatment in his work. This may be surprising in an author who was not only familiar with the operas performed in Spain during the reigns of Philip V and Ferdinand VI, but who was also a great defender of Metastasio as a poet, translating some of his librettos commissioned by the court. In this article we analyse the place of melodrama in his work, showing the influence of Italian poetics, especially Crescimbeni, Gravina, Muratori and Maffei, who understood the genre from Aristotelian ideas about Greek tragedy. As we shall see, the key to his poetics is the contrast between liberal and servile arts, which forces him to place music in an inferior position to poetry.